YBX1: an RNA/DNA-binding protein that affects disease progression - Zheng, Xifeng; Zeng, Feng; Lei, Yan; Li, Yanling; Deng, Jun; Luo, Gengqiu; He, Qian; Zhou, Yanhong (Frontiers in Oncology, 2025)
YBX1 is a member of the Y-box transcription factor family and is a multifunctional RNA/DNA-binding protein characterized by a highly conserved cold shock domain (CSD). YBX1 is localized in both the cytoplasm and nucleus, where it participates in various biological processes such as transcription, translation, and DNA damage repair. YBX1 is upregulated in numerous malignant tumors and is closely associated with tumor progression and poor prognosis, making it a recognized target for cancer therapy. This review introduces the role and mechanism of YBX1 in tumor progression, its function in embryonic development, bone differentiation, cartilage formation, and adipogenesis, the impact of upstream regulatory factors on its function, as well as the relationship between YBX1 and disease prognosis and treatment outcomes. This review aims to provide a comprehensive perspective on the function of YBX1.